Hak Pekerja di Era Gig Economy : Perlindungan Hukum Bagi Pekerja Lepas dan Kontrak - Latri, Akhdan Adityo; Riyanto, Rajwa Khaicirinu; Firdaus, Muhammad Bintang; Arjuna, Muhammad Gaung Syah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Reflecting a paradigm shift in the way people look for work as well as a profound transformation in global economic change, the Gig Economy has become a highly sought after labor market. The gig economy is a job market that relies heavily on the role of independent contractors or contract workers and freelancers to fill temporary and part-time positions. Behind the advantages of the Gig Economy phenomenon, significant challenges are often hidden, especially in terms of legal protection. Therefore, the author conducted studies and research on how Labor Law in Indonesia protects workers in the Gig Economy Era. The writing method that the author uses is qualitative with literature study. Based on the results obtained from the literature, the author can conclude that currently, there is no law in Indonesia that specifically regulates worker protection in the gig economy sector, nor has there been any significant regulatory development related to partnership relations in Indonesia. In fact, the growth of gig economy workers in Indonesia is quite rapid. Gig workers may be protected by the Employment Law, which regulates employment relations between workers and employers. Although gig workers are considered partners, they have rights as employees.